1989
DOI: 10.1002/1097-0142(19891215)64:12<2572::aid-cncr2820641227>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Hormone receptor status in human endometrial adenocarcinoma

Abstract: Steroid receptor levels were determined in 196 samples of endometrial adenocarcinoma: cytosol estradiol receptors (ERc) were measured in 171 samples, cytosol progesterone receptors (PRc) in all samples; nuclear estradiol receptors (ERn) and nuclear progesterone receptors (PRn) in 68 samples; total estradiol receptors (ERt = ERc plus ERn) and total progesterone receptors (PRt = PRc plus PRn) were measured in 68 samples. The ERc levels were 88.2 +/- 8.9 (mean +/- SEM) and ERn were 94.4 +/- 15.6 fmol/mg protein; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

1993
1993
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 24 publications
2
2
0
Order By: Relevance
“…With regard to myometrial invasion, Kauppila, Morris, Fukuda and their associates reported results comparable to ours [13,20,25]. Moreover, Kauppila and colleagues found that the simultaneous presence of ER and PR is associated with a favourable survival for stage-I and -II endometrial tumours [20], and others extended this observation to include recurrent or advanced stage endometrial disease [5,7,9]. Others found that ER [5,13] or PR alone [10] is a better indicator of prognosis, and still others failed to attach any prognostic significance in the receptor status of endometrial malignancies [12,25].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…With regard to myometrial invasion, Kauppila, Morris, Fukuda and their associates reported results comparable to ours [13,20,25]. Moreover, Kauppila and colleagues found that the simultaneous presence of ER and PR is associated with a favourable survival for stage-I and -II endometrial tumours [20], and others extended this observation to include recurrent or advanced stage endometrial disease [5,7,9]. Others found that ER [5,13] or PR alone [10] is a better indicator of prognosis, and still others failed to attach any prognostic significance in the receptor status of endometrial malignancies [12,25].…”
Section: Discussionsupporting
confidence: 93%
“…During malignant transformation, the endometrial cells may lose some or all of their steroid hormone compliment [9,32], and this phenomenon has been connected with partial or complete loss of hormone dependence. In many studies, such tumours were shown to exhibit a more aggressive phenotype, poorer prognosis [5,9,19,20] and an ineffective response to endocrine therapy [5,9,10,32,42].…”
Section: Introductionsupporting
confidence: 80%
See 1 more Smart Citation
“…cer. 3,4 However, in spite of the confirmed expression of sex hormone receptors in other types of cancer such as endometrial carcinomas, 15 carcinomas of the thyroid, 16 renal cell carcinomas, 17 malignant melanoma, 18 and meningiomas, 19 the efficacy of hormonal therapy in these tumors has not yet been established.…”
Section: A B C E F Dmentioning
confidence: 99%